PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR IPAS KELAS V SD NEGERI GAYAMSARI 02 KOTA SEMARANG - Desra Auli Rahman; Eka Titi Andaryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aims of this research are (1) To determine the influence of students' learning motivation on the science and science learning outcomes of class V at SD Negeri Gayamsari 02 Semarang City, (2) To determine the magnitude of the influence of students' learning motivation on the science and science learning outcomes for class V of SD Negeri Gayamsari 02 Semarang City. This research uses a quantitative research type of ex post facto method, this research uses non-probability sampling, data collection techniques in this research are interviews, questionnaires or questionnaires totaling 30 questions and documentation. The results of the research obtained Fcount 10.156 > Ftable 4.15, so it was concluded that students' learning motivation had a significant effect on the science and science learning outcomes for class V of Gayamsari 02 State Elementary School, Semarang City. The result of the constant coefficient analysis is 0.004, which is smaller than 0.005, so H0 is rejected and it is concluded that the regression coefficient for science and science learning outcomes is significant. The influence value of R Square is 0.165, meaning that the influence of students' learning motivation influences science learning outcomes by 16.5% and 83.5% is influenced by other variables.